The legal regulation of service and combat activities of the security and defense sector of Ukraine in crisissituations - Bielai, S. V.; Бєлай, С. В.; Kobzar, O. F.; Кобзар, О. Ф.; Yevtushenko, I. V.; Євтушенко, І. В.; Korniienko, V.V.; Корнієнко, В.В.; ORCID: http://orcid.org/0000-0002-7682-1281; Koba, O. V. (Вісник Національної академії правових наук України. - 2021. - Т. 28, № 2. - С. 76-85, 2021)
Зазначено, що нинішня ситуація в Україні свідчить про потребу нового розвитку теорії військової діяльності правоохоронних органів в умовах врегулювання збройного протистояння в окремих районах Донецької та Луганської областей. Тому на перший план висуваються питання нормативно-правового забезпечення правоохоронних органів у реагуванні на кризові ситуації. Аналіз нормативно-правових актів показує, що правові норми недостатньо чітко сформульовані та неоднозначно трактуються правоохоронними органами. Тому необхідно вдосконалити законодавчий механізм запобігання та реагування на кризові ситуації, що загрожують національній безпеці України. Розкрито сутність та особливості правового регулювання бойових операцій у сфері безпеки та оборони України в кризових ситуаціях та розроблено конкретні практичні рекомендації, науково обґрунтовані пропозиції щодо вдосконалення державного управління у цій галузі.

The article states that nowadays situations in Ukraine shows that the theory of military activity of law enforcement forces needs a new development in the terms of settlement of armed confrontation in separate areas of Donetsk and Luhansk areas. Therefore, the issues of regulatory and legal support of law enforcement agencies in responding to crisis situations come to the fore. The analysis of normative legal acts shows that legal norms are not formulated clearly enough and ambiguously interpreted by law enforcement agencies. Therefore, it is necessary to refine the legislative mechanism for preventing and responding to crisis situations that threaten the national security of Ukraine. Therefore, the purpose of the research is to comprehensively reveal the essence and features of the legal regulations of combat operations of the security and defense sector of Ukraine in crisis situations and to develop specific practical recommendations, scientifically sound proposals for improving State governance in this field. In order to research the best practices of Ukraine on the functioning of Public mechanisms of response of the security and defense sector of Ukraine to crisis situations during the Anti-Terrorist Operation and the Joint Forces Operation in some districts of Donetsk and Luhansk regions, an expert survey of anti-terrorist security experts was conducted. The results of the survey provided an opportunity to identify the main problematic issues in the functioning of the anti-terrorist security system and provide appropriate development proposals. The State authorities today need to focus on improving the organization of management, establishing interagency cooperation between government agencies, increasing the level of pre-training of personnel, a clear definition of tasks for law enforcement units during special operations. Areas of further research will be aimed at developing State mechanisms of responding by the components of the security and defense sector of Ukraine to crisis situations.

Отмечено, что ситуация в Украине свидетельствует о необходимости нового развития теории военной деятельности правоохранительных органов в условиях урегулирования вооруженного противостояния в отдельных районах Донецкой и Луганской областей. Поэтому на первый план выдвигаются вопросы нормативно правового обеспечения правоохранительных органов в реагировании на кризисные ситуации. Анализ нормативно правовых актов показывает, что правовые нормы недостаточно четко сформулированы и неоднозначно трактуются правоохранительными органами. Поэтому необходимо усовершенствовать законодательный механизм предотвращения и реагирования на кризисные ситуации, угрожающие национальной безопасности Украины. Раскрыты сущность и особенности правового регулирования боевых операций в сфере безопасности и обороны Украины в кризисных ситуациях и разработаны конкретные практические рекомендации, научно обоснованы предложения по усовершенствованию государственного управления в этой области.
Правове регулювання службової та бойової діяльності у сфері безпеки та оборони України у кризових ситуаціях
Bielai S. V. The legal regulation of service and combat activities of the security and defense sector of Ukraine in crisissituations / S. V. Bielai, O. F. Kobzar, I. V. Yevtushenko, V. V. Korniienko, O. V. Koba // Вісник Національної академії правових наук України. - 2021. - Т. 28, № 2. - С. 76-85. - DOI: 10.37635/jnalsu.28(2).2021.76-85.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; сектор безпеки і оборони України; security and defense sector of Ukraine; сектор безопасности и обороны Украины; правоохоронні органи; law enforcement agencies; правоохранительные органы; державне управління; governance; государственное управление; система антитерористичної безпеки; anti-terrorist security system; система антитеррористической безопасности; національна безпека; national security; национальная безопасность; правове регулювання; legal regulation; правовое регулирование; військова діяльність; military activity; военная деятельность